Study about Management of Neonatal Seizures: An Approach to Neuropharmacological Aspects - E. Dias; S. Mithun; G. S. Varghese (Research Aspects in Biological Science Vol. 2, 2022)
The present study highlights the Neuropharmacological aspects of drugs involved in the management of newborn convulsion. Seizures in newborns can result in substantial morbidity and even death. Improving prognosis requires quick identification, referral, examination, treatment, and follow-up. Different anti-epileptic medicines, such as phenobarbitone and levetiracetam, have benefits and drawbacks, particularly in terms of neuropharmacology and the treatment of newborn seizures. The clinical value of several medicines used in the management of newborn seizures is discussed in this review. The management of neonatal seizure is challenging especially where there are congenital anomalies of the CNS and metabolic disorder of newborns presenting as neonatal seizures.